Synthesis and Characterization of Some 4f-Metal Ion Complexes of 4[N-(3´ -Nitrobenzalidene)Amino] Antipyrine Thiosemicarbazone - Chakraborti, Indranil (Asian Journal of Chemistry, 2010)
Some 4f-block metal ion coordination compounds of 4[N-(3'nitrobenzalidene) aminol antipyrine thiosemicarbazone (3'-NO2BAAPTS) with the general composition [Ln(3'-NO2BAAPTS)2](ClO4)3 (Ln = La, Pr, Nd, Sm, Gd, Th, Dy or Ho) have been synthesized. The conductance values of these metal coordination compounds in nitrobenzene suggest that the compounds are ionic in nature and all the three perchlorato ions are present outside the coordination sphere. Magnetic, spectral and thermal properties of the compounds have also been investigated. The infrared studies reveal that 3'-NO2 BAAPTS acts as neutral tridentate (N,N,S) ligand. The coordination number of central metal ion is six in all these compounds.